Respuesta :

Answer: 8 – (2 + 1) × (5 – 3) = 2

Step-by-step explanation:

8 – 2 + 1 × 5 – 3 = 2

8 – 2 + 1 × 5 – 3 = 2      ==> notice there is an '8-' in the equation, Let's solve for the difference between 8 and 2.

8 – (2 + 1 × 5 – 3)+(2 + 1 × 5 – 3) = 2 + (2 + 1 × 5 – 3)

8=2 + (2 + 1 × 5 – 3)

8-2=2-2+(2 + 1 × 5 – 3)

6=2 + 1 × 5 – 3   ==> 6 is a multiple of 2 and 3. Let's see how we can convert 2 + 1 × 5 – 3 into the product of 2 and 3

6=(2 + 1) × (5 – 3)

6=3 × 2

6=6√  ==> since this is right, let's substitute the parentheses to the original equation

8 – 2 + 1 × 5 – 3 = 2    ==> 8 – (2 + 1) × (5 – 3) = 2